2021
DOI: 10.1016/j.hrtlng.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HFNC application on mortality and intensive care length of stay in acute respiratory failure secondary to COVID-19 pneumonia

Abstract: Background: In Covid-19 pneumonia, high mortality rates reported in intubated patients have raised noninvasive methods of respiratory support. Objective: We aimed to evaluate the impact of HFNC application on intubation requirement, intensive care length of stay, and short-term mortality in patients with COVID-19 pneumonia. Material-method: Patients receiving oxygen by reservoir mask or HFNC therapy in our intensive care units due to COVID-19 pneumonia were included in the study. Group H consisted of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 28 publications
0
37
1
Order By: Relevance
“…Compared to standard oxygen therapy, HFNO leads to a significant reduction in the rate of intubation, but its effect on mortality was not clear. [1][2][3] In a study by Teng et al with a small number of patients (n = 22), in addition to an improvement to respiratory indexes, the researchers also found a significant decrease in lymphocytes and CRP after 72 hours of HNFO treatment compared to conventional oxygen therapy. 4 The rates of intubation and mortality did not differ between patients receiving NIV or HFNO but a randomized study reported that HFNO was associated with an increased intubation rate compared to Helmet NIV.…”
Section: Resultsmentioning
confidence: 95%
“…Compared to standard oxygen therapy, HFNO leads to a significant reduction in the rate of intubation, but its effect on mortality was not clear. [1][2][3] In a study by Teng et al with a small number of patients (n = 22), in addition to an improvement to respiratory indexes, the researchers also found a significant decrease in lymphocytes and CRP after 72 hours of HNFO treatment compared to conventional oxygen therapy. 4 The rates of intubation and mortality did not differ between patients receiving NIV or HFNO but a randomized study reported that HFNO was associated with an increased intubation rate compared to Helmet NIV.…”
Section: Resultsmentioning
confidence: 95%
“…Studies with smaller cohorts found a decrease in mortality in patients treated with HFNCO. 6,8,11 The higher mortality in the HFNCO failure group in our cohort could be explained by a high rate of complications following the intubation. We found 19.4% ventilation collapse, which is similar to what is found in patients not infected with the SARS-CoV-2, which found a ventilation collapse in 9.6%-29% of cases.…”
Section: Discussionmentioning
confidence: 82%
“…However, the impact of HFNCO on the length of stay in ICU diverges in the literature. 6,8,11 These differences could be explained by a higher frequency of patients presenting less severe infection or by the achievement of early therapeutic limitation in patients treated with HFNCO in our cohort. However, the patients in the HFNCO alone group still presented an average PaO 2 /FiO 2 ratio inferior to 150, testifying to the severity of their pneumonia.…”
Section: Discussionmentioning
confidence: 87%
“…After excluding duplicates and evaluating the full texts of articles, we identified 25 eligible studies (1 RCT, 12 case-control studies, and 12 cohort studies). 14 38 The search and screening process is described in Figure 1 . The main characteristics of the articles included in the meta-analysis are shown in Tables 1 , 2 , 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%